Noninvasive cardiac arrhythmia ablation with particle beams. Issue 11 (13th November 2018) - Graeff, Christian; Bert, Christoph
Abstract : Cardiac arrhythmias are a major health burden, associated with reduced quality of life and substantial morbidity and mortality. Current therapy includes moderately effective medication and catheter‐based ablation of arrhythmogenic substrates in the heart. Catheter interventions frequently have to be repeated due to recurrent arrhythmia, can have rare but severe side‐effects and are less suited especially for potentially lethal left ventricular tachycardia. Noninvasive alternatives are therefore warranted. Photon and ion beam radiotherapy has been studied in animal models and first patient cases have been reported using photons. Ion beams might offer the possibility to greatly reduce dose to surrounding healthy tissue, including critical cardiac substructures. Based on a recently conducted animal study, we report advantages and disadvantages of 4D‐ion beam therapy, and strategies necessary for a clinical transition. Motion management of both respiration and heartbeat are discussed, as well as range uncertainty resulting from both regular motion and interfractional anatomic changes. Image guidance both in 3D and 4D has to be employed for a safe irradiation, but also population‐based data on motion variability and time behavior of interfractional changes are necessary. Range verification could play a crucial role at least during development of clinical protocols. For clinical realization, it appears necessary to suppress or conformally mitigate the large respiratory motion to avoid normal tissue complications. Cardiac motion has to be incorporated into treatment planning, either through adequate range‐considering internal margins or through more conformal strategies such as ECG‐based gating or even 4D‐optimization. The latter strategies would necessitate online 4D image guidance.